Leadership Integrity and Performance: Does Organizational Citizenship Behavior Matter? - Ghulam Muhammad; Aziz Ahmed; Rizwana Rasheed; Muhammad Asif Khan; Farah Siddiq (Journal of Management Practices, Humanities and Social Sciences, 2023)
The purpose of our research is to gauge the impact of leadership integrity on packaging industry performance. Organizational citizenship behavior and job performance were used as the mediators. A close-ended questionnaire was used in order to collect the primary data from the relevant respondents. Those questionnaires were filled by 300 employees of 12 major packaging companies of Pakistan. Data were analyzed by using Smart PLS software v.3.2.8. Results revealed that leadership integrity has a positive significant effect on job performance and organizational citizenship behavior. Similarly, another relationship was found that job performance has a significant positive effect on performance within the context of the packaging industry. Conversely, organizational citizenship behavior does not seem to have a significant positive effect on packaging industry performance. Results also confirm that organizational citizenship behavior and job performance do not have a significant mediating role between leadership integrity and packaging industry performance. The results rejects significant mediating role between leadership integrity and packaging industry performance while evaluating organizational citizenship behavior and job performance.